NEOSARMATISM AND MODERNITY. AN ATTEMPT TO CLARIFY THE LINK - Bohuszewicz, Paweł (Prace Polonistyczne, 2021)
The article is a response to the fragments of Adam Kubiak’s book Rzeczy mniejsze. Dysformia i fiasko: semi-peryferyjne formy kultury (Small Things. Dysformia and Fiasco: Semi Peripheral Forms of Culture) in which the author critically refers to the idea of Neosarmatism. It thus aims to explain the logic behind the concept as well as clarify the relationship between Neosarmatism (as well as Sarmatism) and modernity.